Aplikasi CIKAL Berbantuan Boneka Wayang untuk Meningkatkan Kemampuan Sikap Budaya Sunda pada Anak Usia Dini - Susilawati, Salsa; Aprilianti, Riska; Rochmah, Siti Noor (Indra institute Research & Publication, 2025)
This study was motivated by the lack of children's knowledge in behaving in accordance with Sundanese culture in group B children at Kober X. This study aims to improve the ability of Sundanese cultural attitudes in children after the use of CIKAL application media assisted by puppets. The method used in this research is Classroom Action Research (PTK) with the Kemmis & Mc Taggart model which is carried out in two cycles. Each cycle includes planning, action, observation and reflection stages. The subjects of this study were group B children of Kober X as many as 12 children. The data collection techniques used were performance and documentation. This study uses quantitative analysis in analyzing data. Based on the results of the study, it is known that the CIKAL application media assisted by puppets can improve the ability of Sundanese cultural attitudes in group B children of Kober X. The results of this study indicate the ability of Sundanese cultural attitudes in the aspect of language manners which experienced a significant increase in the category of developing as expected (BSH) which initially only 17% increased after cycle II action to 67% and the category of Developing Very Well by 25%. The aspect of attitude in behaving according to cultural attitudes with the BSH category in the initial condition was only 8%, increasing in cycle II to 75% for the BSH category and the BSB category by 17%.